Higher levels of TIMP-1 expression are associated with a poor prognosis in triple-negative breast cancer. Issue 1 (December 2016) - Cheng, Guangcun; Fan, Xuemei; Hao, Mingang; Wang, Jinglong; Zhou, Xiaoming; Sun, Xueqing
Abstract Background Tissue inhibitor of metalloproteinases-1 (TIMP-1) is a multifunctional protein that can directly regulate apoptosis and metastasis. In this study, we investigated the functional and molecular mechanisms by which TIMP-1 influences triple-negative breast cancer (TNBC). Methods The expression level of TIMP-1 in breast cancer tissues was analyzed using the ONCOMINE microarray database. The overall survival of patients with distinct molecular subtypes of breast cancer stratified by TIMP-1 expression levels was evaluated using Kaplan–Meier analysis. Bisulfate sequencing PCR (BSP) was used to analyze the methylation status of the TIMP-1 promoter. Real-time-PCR (RT-PCR), Western blot and ELISA assays were used to evaluate gene and protein expression in cell lines and human tissue specimens. In addition, TIMP-1 function was analyzed using a series of in vitro and in vivo assays with cells in which TIMP-1 was inhibited using RNAi or neutralizing antibodies. Results We found that serum TIMP-1 levels were strongly enhanced in patients with TNBC and that elevated TIMP-1 levels were associated with a poor prognosis in TNBC. However, TIMP-1 levels were not significantly associated with overall survival in other subtypes of breast cancer or in the overall population of breast cancer patients. We also report the first evidence that the TIMP-1 promoter is hypomethylated in TNBC cell lines compared with non-TNBC cell lines, suggesting that aberrant TIMP-1 expression in TNBC results from reduced DNA methylation. RNAi-mediated silencing of TIMP-1 in TNBC cells induced cell cycle arrest at the G1 phase and reduced cyclin D1 expression. In addition, mechanistic analyses revealed that the p-Akt and p-NF-κB signaling pathways, but not the GSK-3β and MAPK1/2 pathways, are associated with TIMP-1 overexpression in TNBC cells. Moreover, neutralizing antibodies against TIMP-1 significantly decreased the rate of tumor growth in vivo. Conclusions Our findings suggest that TIMP-1 is a biomarker indicative of a poor prognosis in TNBC patients and that targeting TIMP-1 may provide an attractive therapeutic intervention specifically for triple-negative breast cancer patients.